Growth and characterization of succinic acid potassium chloride mixed crystals. (2021) - Vijayalakshmi, M.; Ravindran, B.; Anitha, M.
Abstract: Single crystals of Succinic Acid mixed Potassium Chloride crystals were nucleated from aqueous solution and grown using low-temperature solution growth technique at normal temperature. Current work, concentrates on the growth of Succinic Acid with a combination of a molar ratio 1:1 to Potassium Chloride. The grown crystal was characterized diffraction of X-rays, UV–Vis spectroscopy, Spectrum of Fourier transform infrared, Thermal behaviour and Second- harmonic generation efficiency. Exhibiting the perfection of crystalline nature using the diffraction by X-ray studies was found to be excellent. Fourier Transform Infrared (FTIR) used to locate the presence of functional group. Qualitative calculation was done to predict the functional group from the temperature of FTIR. Recorded UV–VIS-NIR spectrum covers under a range 100–1200 nm exposes the enhanced transparency up to 100% for a very wide range. The thermogravimetric differential the thermal stability analyses were carried out by TG/DSC. SHG of Succinic Acid is found to be slightly increased with the mixed of Potassium Chloride.